2023
DOI: 10.1108/yc-03-2022-1491
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the attitudes and behaviour of Gen Z students towards branded mobile apps in an emerging market: UTAUT2 model extension

Abstract: Purpose With the increasing mobile activity of the Generation Z market (born after 1994), marketers’ interest in this social group is rising. This research paper aims to uncover the relatively unknown attitudes and behaviour of the youth market in an emerging market, South Africa, towards branded mobile applications (apps). Previous studies on mobile marketing have focused on Generation X and Generation Y and generally with a quantitative focus. Design/methodology/approach This study is based on the theoreti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 21 publications
2
23
0
Order By: Relevance
“…All reviews related to one construct were grouped and compared, and variations were derived (Nowell et al 2017), as shown in Figure 2. The constructs were crosscompared to ascertain connections between themes (Axcell 2017). This analysis aims to integrate the themes into a theory that provides an accurate and detailed interpretation of the research (Palmer & Bolderston 2006).…”
Section: Discussionmentioning
confidence: 99%
“…All reviews related to one construct were grouped and compared, and variations were derived (Nowell et al 2017), as shown in Figure 2. The constructs were crosscompared to ascertain connections between themes (Axcell 2017). This analysis aims to integrate the themes into a theory that provides an accurate and detailed interpretation of the research (Palmer & Bolderston 2006).…”
Section: Discussionmentioning
confidence: 99%
“…A thematic analysis was conducted on the transcribed data. Following Axcell and Ellis (2023), quality control centered on credibility, confirmability, dependability, and transferability.…”
Section: Methodsmentioning
confidence: 99%
“…Although privacy issues in mobile apps are a great concern for younger generations (Axcell & Ellis, 2023), they are technology-savvy individuals who highly value positive online experiences and customization, and request smart information technologies to assist them in matching their needs with the most appropriate offerings (Priporas et al, 2017). Younger people are more involved in the use of multiple technological tools to search for relevant and useful information (Agárdi & Alt, 2022), making mutually collaborative relations and ongoing exchanges more conducive.…”
Section: The Moderating Effect Of Agementioning
confidence: 99%
“…Generation Z’s unique purchasing behaviour expectations set them apart from previous generations (Ismail et al , 2021). Researchers suggest their potential to rapidly dominate the global consumer base (Axcell and Ellis, 2023). Generation Z has grown up with the internet at their fingertips, and using social media sites to find inspiration has become the norm (Fan et al , 2023; Goldring and Azab, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Generation Z (Gen-Z), sometimes known as “digital natives”, represents the first generation to become immersed in digital communication (Axcell and Ellis, 2023; Ismail et al , 2021). These are the most recent generations born between 1995 and early 2010 (Chaturvedi et al , 2020; Lina et al , 2022).…”
Section: Introductionmentioning
confidence: 99%